Splenic clearance of rigid erythrocytes as an inherited mechanism for splenomegaly and natural resistance to malaria - Benoit, Henry; Volle, Geoffroy; Akpovi, Hilaire; Gineau, Laure; Roussel, Camille; Papa Alioune Ndour; Felicien Tossou; Suarez, Felipe; Palstra, Friso; Fricot, Aurelie; Chambrion, Charlotte; Solinc, Julien; et al. (bioRxiv, 2022)
In malaria-endemic areas, subjects from specific groups like Fulani have a peculiar protection against malaria, with high levels of IgM but also frequent anemia and splenomegaly. The mechanisms underlying this phenotype remain elusive. In Benin, West Africa, we measured the deformability of circulating erythrocytes in genetically distinct groups (including Fulani) living in sympatry, using ektacytometry and microsphiltration, a mimic of how the spleen clears rigid erythrocytes. Compared to non-Fulani, Fulani displayed a higher deformability of circulating erythrocytes, pointing to an enhanced clearance of rigid erythrocytes by the spleen. This phenotype was observed in individuals displaying markers of Plasmodium falciparum infection. The heritability of this new trait was high, with a strong multigenic component. Five of the top 10 genes selected by a population structure-adjusted GWAS, expressed in the spleen, are potentially involved in splenic clearance of erythrocytes (CHERP, MB, PALLD, SPARC, PDE10A), through control of vascular tone, collagen synthesis and macrophage activity. In specific ethnic groups, genetically-controlled processes likely enhance the innate retention of infected and uninfected erythrocytes in the spleen, explaining splenomegaly, anemia, cryptic intrasplenic parasite loads, hyper-IgM, and partial protection against malaria. Beyond malaria-related phenotypes, inherited splenic hyper-filtration of erythrocytes may impact the pathogenesis of other hematologic diseases. Competing Interest Statement The authors have declared no competing interest.